Health questionnaires - Boelee, Eline; Laamrani, Hammou (2009)
This tool describes the use of school surveys, an important tool that supports both participatory and biomedical research. When epidemiological studies are carried out at the same time, a local quantitative relationship between measured and reported infection rates can be established and the questionnaire can be applied in a larger area to assess prevalence at the level of the reservoir cluster or river basin. Such questionnaires can be adapted for other diseases and to fit varying local circumstances.